2014
DOI: 10.3390/toxics3010001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Neurological Function in Males and Females from Two Substrains of C57BL/6 Mice

Abstract: The C57BL/6 (B6) mouse is the background strain most frequently used for genetically-modified mice. Previous studies have found significant behavioral and genetic differences between the B6J (The Jackson Laboratory) and B6N substrains (National Institutes of Health); however, most studies employed only male mice. We performed a comprehensive battery of motor function and learning and memory tests on male and female mice from both substrains. The B6N male mice had greater improvement in the rotarod test. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 39 publications
2
21
1
Order By: Relevance
“…As we have previously shown that behavioral results including ultrasonic vocalizations (USV) 42 and home-cage activity 43 are sensitive to a small developmental progress during adolescence, we performed our behavioral test battery on two cohorts of mice, one from P22 to P30 and the other from P32 to P40 in order to draw a full picture of the motor ability during adolescence. Because the genetic background and sexes are known to influence behavioral characteristics 42 45 , we performed our experiments on male and female mice of three different inbred strains, C57BL/6N, DBA/2, and FVB/N that are world-wide used in research and are the standard strains in neuroscience with their ability to discern the role of individual genes and the impact of allelic variation along with decreased variability 46 – 49 .…”
Section: Introductionmentioning
confidence: 99%
“…As we have previously shown that behavioral results including ultrasonic vocalizations (USV) 42 and home-cage activity 43 are sensitive to a small developmental progress during adolescence, we performed our behavioral test battery on two cohorts of mice, one from P22 to P30 and the other from P32 to P40 in order to draw a full picture of the motor ability during adolescence. Because the genetic background and sexes are known to influence behavioral characteristics 42 45 , we performed our experiments on male and female mice of three different inbred strains, C57BL/6N, DBA/2, and FVB/N that are world-wide used in research and are the standard strains in neuroscience with their ability to discern the role of individual genes and the impact of allelic variation along with decreased variability 46 – 49 .…”
Section: Introductionmentioning
confidence: 99%
“…Comparative genomic analysis revealed numerous coding variants between B6J (Jackson Laboratory) and B6N (National Institutes of Health) substrains, including 34 single nucleotide variants (32 missense/one nonsense/one splice site), two indels resulting in frameshifts, and 15 structural variants overlapping genes . There are documented substrain‐dependent phenotypic differences in diverse areas, including neurobehavioral/neurologic function, vision, metabolism, and inflammatory response . Understanding and controlling for these differences are critical for experimental validity and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…As the genetic background influences behavioral characteristics 27 , we performed our experiments on three different inbred mouse strains, C57BL/6N, DBA/2, and FVB/N that are world-wide used in research and are the standard strains in neuroscience 24 . Inbred strains have the advantage of discerning the role of individual genes and the impact of allelic variation along with decreasing the variability [28][29][30][31] . Although the C57BL/6N strain is the background strain most frequently used for geneticallymodified mice 16 , the FVB/N strain is preferable for transgenic analysis because its fertilized eggs contain large and prominent pronuclei, which facilitates the microinjection of recombinant genes 32 .…”
mentioning
confidence: 99%